2014
DOI: 10.1186/s12879-014-0639-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological features and prognosis of complicated pyelonephritis: a prospective observational single hospital-based study

Abstract: BackgroundComplicated pyelonephritis (cPN), a common cause of hospital admission, is still a poorly-understood entity given the difficulty involved in its correct definition. The aim of this study was to analyze the main epidemiological, clinical, and microbiological characteristics of cPN and its prognosis in a large cohort of patients with cPN.MethodsWe conducted a prospective, observational study including 1325 consecutive patients older than 14 years diagnosed with cPN and admitted to a tertiary university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 41 publications
4
41
0
Order By: Relevance
“…~20Å), has been noted (Noinaj et al, 2013b). Additionally, the outer membrane layer in proximity to this lateral gate was found to be decreased in phospholipid order and overall thickness, a result consistent with other studies (Gessmann et al, 2014, Sinnige et al, 2014, Burgess et al, 2008. This lateral gate is also structurally conserved within the crystal structure of the TamA protein (Gruss et al, 2013a).…”
Section: Serine Protease Chaperonessupporting
confidence: 73%
See 1 more Smart Citation
“…~20Å), has been noted (Noinaj et al, 2013b). Additionally, the outer membrane layer in proximity to this lateral gate was found to be decreased in phospholipid order and overall thickness, a result consistent with other studies (Gessmann et al, 2014, Sinnige et al, 2014, Burgess et al, 2008. This lateral gate is also structurally conserved within the crystal structure of the TamA protein (Gruss et al, 2013a).…”
Section: Serine Protease Chaperonessupporting
confidence: 73%
“…Risk factors such as physical/functional genitourinary tract abnormalities, catheterization, diabetes, neurological disorders, pregnancy or supressed immunity can predispose patients to chronic UTI (Haider et al, 2010, Turner et al, 2015, Storm et al, 2012, Buonaiuto et al, 2014, De Ruz et al, 2000, Nicolle et al, 1996, Carton, 1992, Kunin et al, 1992. In the nosocomial environemt, catheter-associated UTI (CAUTI) is very common (Al-Hazmi, 2015, Apisarnthanarak et al, 2007.…”
Section: Pseudomonas Aeruginosa Proteus Mirabilis Enterobacter Cloamentioning
confidence: 99%
“…The percentage of patients with negative urine cultures in other studies range from 3.6% to 32.3% depending on the inclusion and exclusion criteria of each study. (7,11) The high percentage of negative urine cultures found could be due to 109 (23.7%) patients having received outpatient antibiotics before the ED visit, although the details of the type of antibiotics and duration of treatment were often unspecified. Another reason could be the commencement of empirical antibiotics in the ED after obtaining blood cultures, with a delay in obtaining urine cultures, particularly for patients who appeared ill. A previous study had shown that negative urine cultures can coexist with imaging-proven pyelonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…The reviewers were not blinded to the purpose of the study. Patients with at least two out of the following three inclusion criteria (11) were recruited into the study: (a) flank pain or costovertebral angle tenderness; (b) urinary symptoms or bacteriuria/pyuria; and (c) fever. Subjects were also included if they were labelled as having pyelonephritis based on imaging (ultrasonography of the kidneys or computed tomography of the kidneys, ureters and bladder) or by the managing team.…”
Section: Methodsmentioning
confidence: 99%
“…The most common organism responsible that is reported to cause pyelonephritis is Escherichia coli followed by Proteus spp, Klebsiella spp etc. [3]. Catheterization, congenital anomalies, immunosuppression therapy, post-transplant status, renal stones, diabetes mellitus are the major risk factors for UTI amongst which diabetes mellitus ranks highest in most of the studies.…”
Section: Discussionmentioning
confidence: 99%